Fractional Anisotropy and Troponin T Parallel Structural Nerve Damage at the Upper Extremities in a Group of Patients With Prediabetes and Type 2 Diabetes – A Study Using 3T Magnetic Resonance Neurography - Jende, Johann M. E.; Kender, Zoltan; Morgenstern, Jakob; Renn, Pascal; Mooshage, Christoph; Juerchott, Alexander; Kopf, Stefan; Nawroth, Peter P.; Bendszus, Martin; Kurz, Felix T. (Frontiers in Neuroscience, 2022)
Background Recent studies have found that troponin T parallels the structural and functional decay of peripheral nerves at the level of the lower limbs in patients with type 2 diabetes (T2D). The aim of this study was to determine whether this finding can also be reproduced at the level of the upper limbs. Methods 10 patients with fasting glucose levels > 100mg/dl (5 with prediabetes and 5 with T2D) underwent magnetic resonance neurography of the right upper arm comprising T2-weighted and diffusion weighted sequences. The fractional anisotropy (FA), an indicator for the structural integrity of peripheral nerves, was calculated in an automated approach for the median, ulnar and radial nerve. All participants underwent additional clinical, serologic, and electrophysiologic assessments. Results High sensitivity troponin T (hsTNT) and HbA1c were negatively correlated with the average FA of the median, ulnar and radial nerve (r=-0.84; p=0.002 and r=-0.68; p=0.032). Both FA and hsTNT further showed correlations with items of the Michigan Hand Outcome Questionaire (r=-0.76; p=0.010 and r=0.87; p=0.001, respectively). A negative correlation was found for hsTNT and HbA1c with the total Purdue Pegboard Test Score (r=-0.87; p=0.001 and r=-0.68; p=0.031). Conclusion This study is the first to find that hsTNT and HbA1c are associated with functional and structural parameters of the nerves at the level of the upper limbs in patients with impaired glucose tolerance and T2D. Our results support the hypothesis that hyperglycemia-related microangiopathy, represented by elevated hsTNT levels, is a contributor to nerve damage in diabetic polyneuropathy.